Integrating Maluku Local Wisdom as English Teaching Material to Build Students’ Character in Globalization Era - Natalia Manuhutu; Abdurrachman Faridi; Frimadhona Syafri; Zulfa Sakhiyya (Universitas Negeri Semarang, 2023)
Integrated teaching with cultural content has become an interesting issue. However, academic circles have not received much attention regarding the integration of Maluku’s local wisdom in teaching English. Education offers students the best opportunity to get in touch with foreign cultures. However, teaching a foreign language is challenging because teachers not only teach vocabulary and grammar, but teachers also need to teach students how and when to use that language. In other words, learning a language also involves learning about culture. It is important to realize that teaching materials must balance the culture of the target language. It would be useful if it could be used in situations where language is required. One of the things in teaching English that must be considered is material that is relevant to the cultural background of our students because that will make the learning process more meaningful. This paper offers a description of ‘papeda’ as one of Maluku's local wisdom that can be used as teaching material to build students’ character with the principles and moral values from their culture that will prepare them to face the era of globalization. It ends with practical examples and technical guidelines for integrating Maluku’s local wisdom into English teaching materials.